Harms of CT scanning prior to surgery for suspected appendicitis. Issue 1 (27th November 2014) - Rogers, William; Hoffman, Jerome; Noori, Naudereh
Abstract : In this brief analysis we compare the risks and benefits of performing a CT scan to confirm appendicitis prior to surgery instead of operating based on the surgeon's clinical diagnosis. We conclude that the benefit of universal imaging is to avoid 12 unnecessary appendectomies but the cost of those 12 avoided surgeries is one cancer death due to the imaging.